Influence of tire reclaimed rubber (TRR) loadings on cure characteristics and mechanical properties of natural rubber/styrene butadiene rubber (NR/SBR) blends / Nurul Jasmine Hassan Nordin ... [et al.] - Hassan Nordin, Nurul Jasmine; Sharif, Adil Fikri; Mamauod, Siti Nur Liyana; Nik Ibrahim, Nik Noor Idayu; Darren, Khooi; Sarkawi, Siti Salina (UiTM Press, 2024)
This investigation delves into the potential utilization of Tire Reclaimed Rubber (TRR) as a filler within Natural Rubber/Styrene Butadiene Rubber (NR/SBR) blends. TRR is obtained from discarded rubber tires and stands as a pertinent resource that necessitates its effective utilization in the production of eco-friendly, value-added rubber-based products. This is due to the rising of rubber waste tires which causes environmental concerns and all sorts of pollution. The TRR filled NR/SBR blends were fabricated using two-roll mills. The loadings of TRR were varied ranging from 20 phr to 100 phr. The aim of this study is to investigate the influence of TRR loading on the cure characteristics and mechanical properties of blends in terms of tensile strength, rebound resilience, hardness, and density. It is found that the MH and ∆ torque exhibited a decreasing trend which would indicate a reduction in crosslink density due to high loading of TRR. Meanwhile, the ts2 and tc95 increased with the increase of TRR loading. Furthermore, the tensile strength, hardness, density, and rebound resilience of blends experience a steady reduction with the incorporation of TRR. The decrement of those properties might be due to the low molecular weight of TRR. Regarding the collective findings, TRR emerges as a potentially viable candidate for waste rubber repurposing, serving as a non-reinforcing filler with optimal utility achieved at a 30 phr loading level.